O lugar da formação de professores para o ensino primário em Moçambique: um estudo de caso do Instituto de Chibututuíne - Bonifácio Obadias Langa (2022)
This Ph.D. dissertation addresses the issue of THE PLACE OF ELEMENTARY TEACHER EDUCATION IN MOZAMBIQUE. In this qualitative research, which can be characterized as a case study, a questionnaire as data production instrument was applied to ten teacher educators and sixty-eight students – all of them from the Teacher Education Institute at Chibututuíne (IFPC), in Mozambique. Semi-structured interviews were carried out with ten people: four managers from the IFPC; one from the National Institute for Education Development; one from the District Services of Education, Youth and Technology in Manhiça; one from the Ministry of Education and Human Development; and three former directors of the IFPC. A documentary analysis was carried out and focused upon the educational legislation of Mozambique, with particular attention to teacher education, to the National Education System and to the national education policy. For data analysis, Bardin's “content analysis” has been used. The survey data revealed that the process of preparing teachers for primary education in Mozambique is corrupted by nepotism, clientelism, allied to neoliberal practices (funding cuts) in the management of the process of teacher education. The profile of teacher educators there does not fit the task of teaching for primary schoolteachers. The management of the teacher education process needs more proactive actions that streamline the education process. They further revealed the urgent need for the transformation of the Pedagogical Influence Zone (ZIP) as a “teacher education place”. The need for institutes to be autonomous in the selection of candidates and faculty was revealed to improve the transparency of the teacher education process and actions. The effort made by the teacher educators is relevant to guarantee the reasonableness of the preparation, however, it is necessary that these actions are systemic. The “10th + 1 year” curricular model does not allow a good preparation of teachers, considering the profile of candidates and teacher educators, the type of knowledge that is intended to be developed, along with the terrible existing material conditions. Considering the current context of teacher preparation for primary education in Mozambique, it can be said that the Institute of Chibututuíne lacks material, human and psycho-technical conditions to operationalize a good preparation of teachers for primary education in this country.